Reforming Civil Service Governance: The Merit System as a Determinant of Performance and Integrity in Modern Bureaucracy - Rina Wahyuni; Rista Ningsih; Salma Afal Alshadiqa; Suci Ramadhani; Yulia Hanoselina; Yuliarti Y (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Bureaucratic reform is a systematic agenda to realize professional, transparent, and service-oriented governance. In this process, the quality of state apparatus is a determining factor in the success of government administration and public services. One of the main instruments in state apparatus management is the implementation of a merit system that places competence, performance, and integrity as the basis for managing human resources of the apparatus. This study aims to analyze the role of the merit system as a determinant of the performance and integrity of modern bureaucracy, identify obstacles in its implementation, and formulate a strategy for restructuring apparatus governance based on meritocracy. The study uses a qualitative approach with a library research method through the review of literature, scientific journals, laws and regulations, and related official documents. The research analysis is based on Max Weber's rational-legal bureaucracy theory, the concept of good governance, and the theory of meritocracy in public administration. The results show that the implementation of a merit system can increase the professionalism of state apparatus, encourage objectivity in job promotions, strengthen bureaucratic integrity, and improve the quality of performance and public services. However, the implementation of the merit system still faces various obstacles, such as political interference, a culture of patronage, weak oversight, limited staff competency, and a suboptimal digital civil service management system. Therefore, strengthening leadership commitment, accountable oversight, staff competency development, and organizational culture transformation are needed to support the realization of a modern, professional, and integrated bureaucracy.